2010
DOI: 10.1152/jn.91241.2008
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Selection of Contra- and Ipsilateral Forelimb Movements by the Dorsal Premotor Cortex in Monkeys

Abstract: Kurata K. Conditional selection of contra-and ipsilateral forelimb movements by the dorsal premotor cortex in monkeys. J Neurophysiol 103: 262-277, 2010. First published November 4, 2009 doi:10.1152/jn.91241.2008. It has been suggested that the dorsal premotor cortex (PMd) may contribute to conditional motor behavior. Thus when a selection is instructed by arbitrary conditional cues, it is possible that the unilateral PMd affects behavior, regardless of which arm, contra-or ipsilateral, is to be used. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
(111 reference statements)
1
8
0
Order By: Relevance
“…In the cerebro-cerebellar loop, delay period activities were observed in M1/PM (Tanji and Evarts, 1976;Weinrich and Wise, 1982;Kurata and Wise, 1988;Crammond and Kalaska, 1994;Kakei et al, 1999Kakei et al, , 2001Nakayama et al, 2008;Kurata, 2010), in putative PN (as MFs, present study) and in the motor thalamus (Kurata, 2005) during an arm movement task. We also observed delay activity of DN neurons in the same task used here (unpublished observations).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…In the cerebro-cerebellar loop, delay period activities were observed in M1/PM (Tanji and Evarts, 1976;Weinrich and Wise, 1982;Kurata and Wise, 1988;Crammond and Kalaska, 1994;Kakei et al, 1999Kakei et al, , 2001Nakayama et al, 2008;Kurata, 2010), in putative PN (as MFs, present study) and in the motor thalamus (Kurata, 2005) during an arm movement task. We also observed delay activity of DN neurons in the same task used here (unpublished observations).…”
supporting
confidence: 55%
“…Indeed, we found that there were common features in the delay activity of M1/PM neurons and the MFs. First, as observed in PM and M1 (Tanji and Evarts, 1976;Weinrich and Wise, 1982;Kurata and Wise, 1988;Crammond and Kalaska, 1994;Nakayama et al, 2008;Kurata, 2010), most MFs had delay activity triggered by instruction cue presentation. Second, many MFs showed modulation changes that started more than 1000 ms after instruction cue presentation, i.e., after the earliest timing of go signal.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Indeed, a number of studies have probed how neural circuits represent laterality of reaching movements in macaque monkeys. Integration of arm specific and arm independent information has been found in the posterior parietal cortex [1][2][3] , premotor cortex [4][5][6][7][8][9] , and primary motor cortex (M1) [10][11][12] , although the outputs from M1 have been identified as mostly contra-lateral 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Neural activity in these areas is strongly modulated by visual object properties 17,18 , extrinsic goals 19 , performed grip types 20,21 , and preparatory activity in these areas can be used to decode the visual properties of objects and complex hand shapes required to grasp a diverse range of objects [22][23][24] , as well as predict reaction times 25 . Although laterality has been studied in ventral premotor cortex, these studies either employed no delay period 26 , simple movements 10 , or required only reaching movements 6,7,27 . Additionally, to our knowledge, no electrophysiological studies of laterality have been undertaken in AIP.…”
Section: Introductionmentioning
confidence: 99%